2021
DOI: 10.3390/nu13041318
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Neuroprotective Role of Free and Encapsulated Quercetin Mediated by miRNA against Neurological Diseases

Abstract: Chronic neuroinflammation is a pathological condition of numerous central nervous system (CNS) diseases such as Parkinson’s disease, Alzheimer’s disease, multiple sclerosis, amyotrophic lateral sclerosis and many others. Neuroinflammation is characterized by the microglia activation and concomitant production of pro-inflammatory cytokines leading to an increasing neuronal cell death. The decreased neuroinflammation could be obtained by using natural compounds, including flavonoids known to modulate the inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 119 publications
0
39
0
Order By: Relevance
“…New therapeutic horizons were opened with obtaining recent nano-pharmaceutical formulations such as micelles, phytosomes or encapsulated QUR, that increase its brain concentration. (Benameur et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…New therapeutic horizons were opened with obtaining recent nano-pharmaceutical formulations such as micelles, phytosomes or encapsulated QUR, that increase its brain concentration. (Benameur et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these limitations, it is still able to cross the BBB, and studies in animals have confirmed its biological effectiveness in medical conditions. Furthermore, delivery of quercetin in the form of nanoparticles, such as superparamagnetic iron oxide nanoparticles [202] and solid lipid nanoparticles [208], may help in overcoming this problem and facilitate its bioavailability and distribution in the brain, thus ensuring better biological efficacy [233].…”
Section: Quercetinmentioning
confidence: 99%
“…Quercetin has been reported to possess several biological properties, including antioxidative and anti-inflammatory effects [ 32 ]. Due to the antioxidative and anti-inflammatory properties of quercetin, the consumption of quercetin has been recently reported to exert potential human health benefits [ 33 ]. Notably, quercetin has been suggested to improve insulin resistance by inhibiting the synthesis and secretion of proinflammatory mediators [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the antioxidative and anti-inflammatory properties of quercetin, the consumption of quercetin has been recently reported to exert potential human health benefits [ 33 ]. Notably, quercetin has been suggested to improve insulin resistance by inhibiting the synthesis and secretion of proinflammatory mediators [ 33 ]. Exogenous quercetin contributes to many physiological functions that may prevent and treat inflammatory, metabolic, and ischemic diseases [ 34 ].…”
Section: Introductionmentioning
confidence: 99%